Evaluation of misai kucing (orthosiphon stamineus) extract on diabetic cell line - Adnan, Adieya Atyrrah; Khayat, Mohd Ezuan; Halim, Murni; Wasoh, Helmi; M.Sobri, Zulfazli (Malaysian Society for Molecular Biology and Biotechnology, 2024)
Orthosiphon stamineus, locally known as Misai Kucing, is a traditional medicinal plant used to treat various ailments, including diabetes. However, limited scientific research has confirmed its anti-diabetic potential. This study aimed to evaluate the effects of O. stamineus extracts on diabetic cell lines. The plant was dried, ground, and extracted using four different solvents: water, ethanol, ethyl acetate, and hexane. The crude yield from these extractions was highest in water, followed by ethanol, ethyl acetate, and hexane. In vitro toxicity assays were conducted on the 3T3-L1 pre-adipocyte cell line to assess the viability of cells treated with water and ethanolic extracts. The extracts were tested at various concentrations to determine their toxicity. Concentrations below 1.25 x 10-1 mg/mL for both extracts were non-toxic, with more than 50% viable cells observed. However, at higher concentrations (1.25 x 10-1 mg/mL), the water extract showed toxicity. Non-toxic concentrations (ranging from 0 to 0.06 mg/mL) were used to measure glucose uptake in the 3T3-L1 diabetic cell line by incubating the cells with a fluorescent D-glucose analog, 2-NBDG. The results showed a reduction in 2-NBDG uptake in cells treated with the extracts compared to untreated cells, indicating the potential to influence glucose metabolism. This suggests that water and ethanolic extracts of O. stamineus could play a role in managing diabetes by improving glucose regulation, supporting its traditional use as an anti-diabetic remedy and highlighting its medicinal potential.